Adherence to antirretroviral therapy by patients with HIV in Brazil and factors that harmful it: an integrative review (Research, Society and Development, 2023)
Objective: To analyze and summarize the factors related to adherence to antiretroviral therapy (ART) in people with HIV/AIDS in Brazil and their main barriers to continuity. Methodology: Integrative literature review using the Scientific Electronic Library Online (SciELO), PUBMED and Latin American and Caribbean Literature (LILACS) databases based on the combination of Health Sciences Descriptors (DeCS/MeSH). Results: ART represents the main way to control HIV infection, making its adherence a complex and multifactorial process. The first six months of treatment are decisive in the success of medication consumption. However, the regularity of the use of ART permeates several conditions, such as: social context, income, education, adverse effects, stigma, use of alcohol and other drugs, in addition to the support network and receptivity in the health system. Therefore, in order for the therapeutic process to continue, it is essential to effectively welcome and identify the demands of users in the health service, so that they feel safe and encouraged to remain in treatment. Conclusion: According to the survey carried out, a weakness in adherence to ART was perceived, which draws attention to intervention measures, such as: motivational interview, use of mobile applications, SMS and phone calls, contributing to the care practice and comprehensive health monitoring of these individuals.